Saving grace and the environment: how states influence the Christian steward agenda - Lewis, Amy, author; Yasar, Gamze, advisor; Davis, Sandra, committee member; Vasudevan, Ramaa, committee member (Colorado State University. Libraries, 2010)
Explanations regarding the success and behavior of new social movements rely largely on postmaterialist assumptions. An examination of the Christian Stewards new social movement in the United States and Canada and its varying levels of success in these two different states calls into question the explanatory relevance of postmaterialist arguments as they pertain to new social movement theory and offers an alternative explanation in the form of social opportunity structure.
Covers not scanned.
Keywords: Christian stewardship; Environmentalism -- United States; Environmentalism -- Canada